Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1063/5.0037551
|View full text |Cite
|
Sign up to set email alerts
|

Probing the structural properties of the water solvation shell around gold nanoparticles: A computational study

Abstract: While subjected to radiation, gold nanoparticles (GNP) have been shown to enhance the production of radicals when added to aqueous solutions. It has been proposed that the arrangement of water solvation layers near the water-gold interface plays a significant role. As such, the structural and electronic properties of the first water solvation layer surrounding GNP of varying sizes were compared to bulk water using classical molecular dynamics, quantum and semiempirical methods. Classical molecular dynamics was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 76 publications
(112 reference statements)
0
16
0
Order By: Relevance
“…39 Yet, a shortcoming of most previous studies is the absence of explicit metal polarizability and its concomitant interfacial effects on interface hydration, adsorption, polarization, and charge transfer. 40 The effects of induced charges in metal surfaces have long been known to be significant in vacuum from an electronic-structure perspective, 41 whereas the effects on interfaces with aqueous solutions, biomolecules, and ionic liquids have only started to be addressed recently in a quantitative manner, both from the quantum and classical perspectives. 27,32,42 Furthermore, recent studies of induction effects on the hydration of graphene by using the selfconsistent atomic polarization model of graphene 43 and the fluctuating-charge technique of constant applied potential molecular dynamics (CAPMD) 44 show the importance of explicit polarizability of quasi-metallic graphene.…”
mentioning
confidence: 99%
“…39 Yet, a shortcoming of most previous studies is the absence of explicit metal polarizability and its concomitant interfacial effects on interface hydration, adsorption, polarization, and charge transfer. 40 The effects of induced charges in metal surfaces have long been known to be significant in vacuum from an electronic-structure perspective, 41 whereas the effects on interfaces with aqueous solutions, biomolecules, and ionic liquids have only started to be addressed recently in a quantitative manner, both from the quantum and classical perspectives. 27,32,42 Furthermore, recent studies of induction effects on the hydration of graphene by using the selfconsistent atomic polarization model of graphene 43 and the fluctuating-charge technique of constant applied potential molecular dynamics (CAPMD) 44 show the importance of explicit polarizability of quasi-metallic graphene.…”
mentioning
confidence: 99%
“…47 In order to inspect the microscopic structure of interfacial water at polarized AuNPs in more detail, we analyzed the water orientation with respect to the NP (Figure 2e), which can be determined by two angles, α and β, as proposed in a recent work. 37 Angle α is defined as the angle between the dipole of the water molecule and the vector formed between the center of the NP and the oxygen atom of the water molecule; whereas β denotes the angle between the normal of the water molecule and the vector formed between the center of the NP and the oxygen atom of the water molecule; see the schematic diagram in Figure S1 in the Supporting Information. According to this definition, the criteria for the 'up' and 'down' configurations are α < 0.4π and α > 0.6π, respectively, regardless of β; the flat configuration is characterized by 0.45π < α < 2 3 π and either β < 1 6 π or β > 5 6 π; and the dangling configuration corresponds to the remaining configurations.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, water and ionic contributions are balancing each other, while polarizability influences the balance. In fact, classical non-polarizable MD studies have found that the rearrangement of water molecules at the interface is actually disrupted by the presence of ions, 37 showing that the proportion of dangling water molecules change according to the size of the NP and the concentration of ions. This has consequences for water hydrolysis in the presence of gold NPs as an example.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations